THEORETICAL FOUNDATIONS OF THE FINANCIAL CONDITION ANALYSIS AND AUDIT OF ENTERPRISES OPERATING ON THE BASIS OF PUBLIC-PRIVATE PARTNERSHIP (Eureka Journal of Civil, Architecture and Urban Studies, 2026)
The article examines the theoretical foundations of accounting for the analysis and audit of the financial condition of enterprises operating on the basis of public-private partnership (PPP) in Uzbekistan. The study analyzes the application of fundamental accounting principles, financial analysis methods, and audit processes in PPP enterprises. A mixed methodology was employed, including qualitative analysis of legislation and enterprise financial reports, as well as quantitative analysis of financial indicators. The results demonstrate that modern accounting and audit methods significantly enhance financial transparency; however, issues related to data quality and specialist qualifications persist. Recommendations based on international experience have been adapted to Uzbekistan’s conditions.
Keywords: Public-private partnership, accounting, financial analysis, audit, financial condition, Uzbekistan.